2022
DOI: 10.1177/00027162221119348
|View full text |Cite
|
Sign up to set email alerts
|

Nonresident Fathers and the Economic Precarity of Their Children

Abstract: This study examines the relationship between nonresident fathers and their children’s economic precarity. We use a racially, ethnically, and socioeconomically diverse sample of children in large U.S. cities and consider a comprehensive set of measures of the involvement of nonresident fathers in their lives. We evaluate both voluntary and involuntary (court-ordered child support) involvement of fathers, and we look at material hardship and income-to-poverty ratio as measures of children’s economic precarity. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Some recent literature demonstrates most nonresident parents contribute some in-kind or informal support and that informal support is related to both quality and quantity of time spent with children (Waller et al, 2018). Informal and in-kind support are also correlated with important child well-being outcomes (Nepomnyaschy et al, 2014(Nepomnyaschy et al, , 2020(Nepomnyaschy et al, , 2022 and these forms of support may be associated with, for example, reductions in behavior problems to a greater extent than formal support (Nepomnyaschy et al, 2020). While informal/in-kind support is shown to dissipate over the first few years following divorce or separation (Nepomnyaschy & Garfinkel, 2010;Sariscsany et al, 2019), formal support increases and remains a meaningful source of support, helping resident parents cover child-related costs (Sariscsany et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some recent literature demonstrates most nonresident parents contribute some in-kind or informal support and that informal support is related to both quality and quantity of time spent with children (Waller et al, 2018). Informal and in-kind support are also correlated with important child well-being outcomes (Nepomnyaschy et al, 2014(Nepomnyaschy et al, , 2020(Nepomnyaschy et al, , 2022 and these forms of support may be associated with, for example, reductions in behavior problems to a greater extent than formal support (Nepomnyaschy et al, 2020). While informal/in-kind support is shown to dissipate over the first few years following divorce or separation (Nepomnyaschy & Garfinkel, 2010;Sariscsany et al, 2019), formal support increases and remains a meaningful source of support, helping resident parents cover child-related costs (Sariscsany et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that formal child support is an important part of a resident parent's income and thus plays an essential role in the economic well‐being of resident‐parent families, especially families who would otherwise be poor (Berger & Font, 2015; Sorensen, 2016). Receipt of child support is known to be associated with lower poverty among children in separated and divorced families (Bartfeld, 2000; Sorensen, 2016), though some work shows that this is primarily true for higher amounts of support (Nepomnyaschy et al, 2022). Cancian and Meyer's (2005) analysis of Wisconsin's state administrative data showed that child support is a key income source for low‐income families, reducing pre‐child‐support poverty rates by 16% and closing the poverty gap by an average of 44%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Though note that except in cases with extremely high orders, payment amounts rise with order amounts; Hodges et al., 2020.) Moreover, while substantial orders may be burdensome for low‐income nonresident parents, many nonresident parents with low earnings have children living in low‐income households (Ha et al., 2018; Nepomnyaschy et al., 2022). In the absence of sufficient resources to provide children with basic needs, setting minimal or zero‐dollar orders leaves resident parents with the difficult responsibility for providing for the children financially, as well as serving as their children's principal caretakers.…”
Section: Child Support Orders and Enforcementmentioning
confidence: 99%
“…Thus, for some separated parents with low incomes, child support merely reshuffles poverty by transferring resources from low-income noncustodial parents to low-income, custodial parents. Finally, some new research (see Nepomnyaschy and colleagues, this volume) emphasizes the importance of noncustodial parental involvement with children and the importance of their voluntary contributions of money and time to their children’s well-being.…”
Section: Child Support Receiptsmentioning
confidence: 99%